Metakomunikasi Anak Usia Dini: Analisis Dari Permainan Sosial Berpura-Pura - Mukhlis, Akhmad (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2017)
This article is an overview of research on early childhood metacommunication. The analysis conducted on several journal articles and books to find identification and explain the inconsistencies in the results of research. First, the overview of the conceptual, developmental and functional aspects of metacommunication in early chilhood social pretend play. This section describes the definition, theory and the development of metacommunication during social pretend play may make an important contribution to the early development of metacognition and self-regulation. Second, reviews about the importance of the involvement of adults in social pretend play While this review highlights some important conceptual, developmental and pedagogical issues in relation to metacommunicaton in social pretend play, these aspects clearly require elaboration. Suggestions are made for further research on metacommunciation development, and the conditions which support its emergence and development.